Characteristics, risk factors, and outcomes related to Zika virus infection during pregnancy in Northeastern Thailand: A prospective pregnancy cohort study, 2018-2020. - Jurai Wongsawat; Somsak Thamthitiwat; Victoria J Hicks; Sumonmal Uttayamakul; Phanthaneeya Teepruksa; Pongpun Sawatwong; Beth Skaggs; Philip A Mock; John R MacArthur; Inthira Suya; Patranuch Sapchookul; Paul Kitsutani; et al. (Public Library of Science (PLoS), 2024)
Background In response to the 2015-2016 Zika virus (ZIKV) outbreak and the causal relationship established between maternal ZIKV infection and adverse infant outcomes, we conducted a cohort study to estimate the incidence of ZIKV infection in pregnancy and assess its impacts in women and infants. Methodology/principal findings From May 2018-January 2020, we prospectively followed pregnant women recruited from 134 participating hospitals in two non-adjacent provinces in northeastern Thailand. We collected demographic, clinical, and epidemiologic data and blood and urine at routine antenatal care visits until delivery. ZIKV infections were confirmed by real-time reverse transcriptase polymerase chain reaction (rRT-PCR). Specimens with confirmed ZIKV underwent whole genome sequencing. Among 3,312 women enrolled, 12 (0.36%) had ZIKV infections, of which two (17%) were detected at enrollment. Ten (83%, 3 in 2nd and 7 in 3rd trimester) ZIKV infections were detected during study follow-up, resulting in an infection rate of 0.15 per 1,000 person-weeks (95% CI: 0.07-0.28). The majority (11/12, 91.7%) of infections occurred in one province. Persistent ZIKV viremia (42 days) was found in only one woman. Six women with confirmed ZIKV infections were asymptomatic until delivery. Sequencing of 8 ZIKV isolates revealed all were of Asian lineage. All 12 ZIKV infected women gave birth to live, full-term infants; the only observed adverse birth outcome was low birth weight in one (8%) infant. Pregnancies in 3,300 ZIKV-rRT-PCR-negative women were complicated by 101 (3%) fetal deaths, of which 67 (66%) had miscarriages and 34 (34%) had stillbirths. There were no differences between adverse fetal or birth outcomes of live infants born to ZIKV-rRT-PCR-positive mothers compared to live infants born to ZIKV-rRT-PCR-negative mothers. Conclusions/significance Confirmed ZIKV infections occurred infrequently in this large pregnancy cohort and observed adverse maternal and birth outcomes did not differ between mothers with and without confirmed infections.